South China sea issue and Southeast Asian countries’ perception of China’s image: An empirical study based on GDELT big data - Wei, Zibo; Chen, Xuan; Tang, Genli; Xie, Yishuai (PloS one, 2025)
How does the South China Sea issue affect China’s image in Southeast Asian countries? Has it diminished Southeast Asian countries’ perception of China? Based on the Global Database of Events, Language, and Tone (GDELT) from 2010 to 2024, this study empirically examines the impact of the South China Sea issue on Southeast Asian countries’ perception of China’s image using a panel multiple linear regression model. The empirical results show a significant positive correlation between the South China Sea issue and Southeast Asian countries’ perception of China’s image. Specifically, the positive impact of verbal events, material events, and the scale of events related to the South China Sea significantly enhances the positive evaluation and recognition of China among Southeast Asian countries. Additionally, GDP plays a moderating role in this process, weakening the positive impact of verbal events, factual events, and the scale of South China Sea events on China’s positive evaluation and recognition. In Southeast Asian countries with territorial disputes and sovereignty conflicts with China, the influence of factual events and the scale of South China Sea events on the perception of China’s image is more pronounced. In contrast, in Southeast Asian countries without such disputes, verbal events have a more significant impact on their perception of China’s image.